Interactive Videos for Facilitating Reading Activity in an Inclusive Class - Narayana, Komang Ksatria; Utami, I G A Lokita Purnamika; Ana, I Ketut Trika Adi (Journal of Educational Study, 2026)
Despite growing attention to inclusive education, there is still limited empirical research on the development and validation of interactive multimodal English learning videos that integrate sign language and visual supports for deaf-mute and regular students within the Merdeka Curriculum at the elementary level. This study aims to develop interactive videos as multimodal learning materials for teaching English to fourth-grade students in an inclusive classroom. Using the ADDIE instructional design model (Analysis, Design, Development, Implementation, Evaluation), the research enhances reading interest and comprehension among deaf-mute and regular students through sign language integration, visual aids, and interactive exercises. Needs analysis revealed that inclusive students require visually engaging, adaptive materials. The videos align with the Merdeka Curriculum, featuring clear visuals, structured narration based on Pancasila values, and inclusive learning support. Instruments used include interview guides, researcher journals, development progress sheets, expert judgments, and practicality questionnaires. Expert validation showed high scores: 4.625 (content expert) and 4.75 (media expert), categorized as very good. Practicality tests scored 4.3 (students) and 4.75 (teachers), indicating high effectiveness. Results show that interactive videos improve accessibility, engagement, and reading comprehension for students with special needs. Challenges include limited technology access and the need for teacher training. The study concludes that multimodal learning significantly benefits inclusive education and recommends further research on scalability and long-term impact.